Acheulo-Yabrudian and Early Middle Paleolithic at Hayonim Cave (Western Galilee, Israel): Continuity or break?. Issue 139 (February 2020) - Meignen, Liliane; Bar-Yosef, Ofer
Abstract: The long archeological sequence exposed during our renewed excavations in Hayonim Cave sheds new light on the striking technological changes observed at the boundary between the Acheulo-Yabrudian (end of the Lower Paleolithic) and Early Middle Paleolithic in the Levant, as well as on their meaning in terms of population movements. The recent, as yet unpublished, technological studies highlight a clear technological break between these two entities. In Hayonim, the Acheulo-Yabrudian assemblages found at the bottom of the archeological sequence display the specific combination of bifacial shaping and the production of thick, often cortical, flakes frequently shaped into scrapers by Quina retouch. Neither of these lithic production systems is observed in the succeeding Levantine Middle Paleolithic assemblages. In contrast, the Early Middle Paleolithic is characterized by the expansion and diversification of the Levallois production system in its full-fledged form, the emergence of a specific Laminar technology, and a high proportion of retouched tools made on elongated blanks (points and blades). These technological features are unknown in the previous Acheulo-Yabrudian assemblages in the cave. Based on this information, we attempt to determine if the observed changes in stone tool production strategies resulted from an autochthonous development or a dispersal out of Africa.